Dual p38MAPK and MEK inhibition disrupts adaptive chemoresistance in mesenchymal glioblastoma to temozolomide - Cheng, Hong Sheng (2024)
Background: Precision treatment of glioblastoma is increasingly focused on molecular subtyping, with the mesenchymal subtype particularly resistant to temozolomide. Here, we aim to develop a targeted therapy for temozolomide resensitization in the mesenchymal subtype. Methods: We integrated kinomic profiles and kinase inhibitor screens from patient-derived proneural and mesenchymal glioma-propagating cells and public clinical datasets to identify key protein kinases implicated in temozolomide resistance. RNAseq, apoptosis assays, and comet assays were used to examine the role of p38MAPK signaling and adaptive chemoresistance in mesenchymal cells. The efficacy of dual p38MAPK and MEK/ERK inhibition using ralimetinib (selective orally active p38MAPK inhibitor; phase I/II for glioblastoma) and binimetinib (approved MEK1/2 inhibitor for melanoma; phase II for high-grade glioma) in primary and recurrent mesenchymal tumors was evaluated using an intracranial patient-derived tumor xenograft model, focusing on survival analysis. Results: Our transcriptomic-kinomic integrative analysis revealed p38MAPK as the prime target whose gene signature enables patient stratification based on their molecular subtypes and provides prognostic value. Repurposed p38MAPK inhibitors synergize favorably with temozolomide to promote intracellular retention of temozolomide and exacerbate DNA damage. Mesenchymal cells exhibit adaptive chemoresistance to p38MAPK inhibition through a pH-/calcium-mediated MEK/ERK pathway. Dual p38MAPK and MEK inhibition effectively maintain temozolomide sensitivity in primary and recurrent intracranial mesenchymal glioblastoma xenografts. Conclusions: Temozolomide resistance in mesenchymal glioblastoma is associated with p38MAPK activation. Adaptive chemoresistance in p38MAPK-resistant cells is mediated by MEK/ERK signaling. Adjuvant therapy with dual p38MAPK and MEK inhibition prolongs temozolomide sensitivity, which can be developed into a precision therapy for the mesenchymal subtype.